Prediction and spatial variability of soil dynamic properties in sugar cane fields of São Paulo State Brazil - Silva, Reginaldo Barboza da [UNESP]; Lanças, Kleber Pereira [UNESP]; Miranda, EEV (Wageningen Academic Publishers, 2005)
The objective of this work was to model and diagnose the spatial variability of soil load support capacity (SLSC) in sugar cane crop fields, as well as to evaluate the management impact on São Paulo State soil structure. The investigated variables were: pressure preconsolidation (sigma(p)), apparent cohesion () and internal friction angle (). The conclusions from the results were that the models and spatial dependence maps constitute important tools in the prediction and location of the mechanical internal strength of soils cultivated with sugar cane. They will help future soil management decisions so that soil structure sustainability will not be compromised.
Keywords: soil compaction; preconsolidation pressure; shear stress; sugar cane; trafficability